Structural Power in Sustainability Transitions: Case Studies of Energy Storage Integration Into Regional Transmission Organization Decision Processes - Lenhart, Stephanie; Fox, Dalten (Frontiers in Climate, 2021)
Highly technical rules for regional electricity markets shape opportunities for new technologies and the pace of transition to a cleaner and more distributed power system. We compare three case studies of regional transmission organizations and identify common mechanisms that describe the relationship between institutional design and administrative policy decisions. For each case study, we compare industry actors, old and new, across these case studies to better understand structural power and institutional stability through four mechanisms drawn from the literature: 1) self-reinforcing interests, 2) participation in and position of groups, 3) influence over communication and information, and 4) control over problem framing and pace of decisions. A focus on the mechanisms that operate within RTO governance provides insight into needed RTO governance reform.